Skin test in drug eruption Five years experience at Dr. Cipto Mangunkusumo General Hospital, Jakarta (Faculty of Medicine Universitas Indonesia, 2004)
Side effect of a drug should always considered by the physician in prescribing the drug for patients. Drug eruption could be very severe and re-exposure to traces of possible causative drugs may induce the same or even fatal clinical type of skin lesion. The aim of the study was to evaluate the role of skin test, an alternative in-vivo methods, in determining the cause of drug eruption. A retrospective study on results of skin test (patch and prick test) in drug eruption was conducted during 5 years period (1998-2002), with special interest on clinical type of lesion. The most prominent clinical type were fixed drug eruption(FDE), urticaria, eczematous eruption, exanthematous eruption, and erythroderma. Skin test was done on 125 out of 746 patients with drug eruption, and 34.4% gave positive results. In some mild cases of urticaria and FDE oral provocation test was done with special precaution. The results showed that skin test could be considered as an alternative, safe and relatively easy way to the oral challenge test to find the causative drug in drug eruption, especially the severe form. (Med J Indones 2004; 13: 81-5)Keywords: skin test, drug eruption, cutaneous adverse drug reaction (CADR).